(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Agricultural practises in poor nations are typically done by hand using blunt instruments, while fossil fuel use in wealthy countries has resulted in significant global warming and environmental damage. The objective of the research was to establish how much renewable energy is utilized in agricultural activities, as well as its limits and potential remedies. Renewable energy source explored include biomass, geothermal, wind, sun, hydropower, and fuelwood. Sustainable energy farming in agriculture to limit the quantity of carbon emitted into the environment by converting fossil fuel burning to renewable energy sources. Agriculturalists produces capital worldwide input and integrating them with energy-saving methods. Green energy lets companies save cash while simultaneously combating the effects of global warming. Wind, hydropower as well as solar electricity, plus biomass are examples of potential renewable energy sources for the rural agricultural industry. They may be utilized to decrease the energy gap in rural as well as metropolitan region while simultaneously reducing the pace of environmental degradation. In order to produce, manage, monitor, and evaluate renewable energy, sufficient is needed to educate and transmit this information to rural region. The rising need for food, combined with the fluctuating charge on fossil fuel, has driven a hunt for ecologically acceptable energy sources. Energy is a significant cost in the production management. The use of a sustainable energy grid to monitor green-house environment reduces consumption of fuel plus improves the sustainability of green-house building.